2024
DOI: 10.1161/hypertensionaha.123.19939
|View full text |Cite
|
Sign up to set email alerts
|

Basic Mechanisms of Brain Injury and Cognitive Decline in Hypertension

Caroline E. Baggeroer,
Francis E. Cambronero,
N. Anna Savan
et al.

Abstract: Dementia affects almost 50 million adults worldwide, and remains a major cause of death and disability. Hypertension is a leading risk factor for dementia, including Alzheimer disease and Alzheimer disease–related dementias. Although this association is well-established, the mechanisms underlying hypertension-induced cognitive decline remain poorly understood. By exploring the mechanisms mediating the detrimental effects of hypertension on the brain, studies have aimed to provide therapeutic insights and strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 104 publications
0
8
0
Order By: Relevance
“…10,[13][14][15][16][17][18][19][20][21][22][23] In relation to the brain, hypertension is a risk factor for carotid artery and intracranial atherosclerosis, dysregulation of cerebral blood flow (CBF), and classic ischemic strokes. [24][25][26] Cerebral small vessel disease-a key cause of reduced CBF, microinfarcts, microbleeds, blood-brain barrier (BBB) dysfunction, and abnormalities of the perivascular space-is also driven by hypertension. 5,14,[25][26][27][28][29] Both large vessel disease and small vessel disease promote the vascular component of reduced brain health: loss of cognitive reserve, cognitive impairment, dementias, and neurodegeneration (Figure 1).…”
Section: Compendium: Circadian Mechanisms In Cardio/ Cerebrovascular ...mentioning
confidence: 99%
See 4 more Smart Citations
“…10,[13][14][15][16][17][18][19][20][21][22][23] In relation to the brain, hypertension is a risk factor for carotid artery and intracranial atherosclerosis, dysregulation of cerebral blood flow (CBF), and classic ischemic strokes. [24][25][26] Cerebral small vessel disease-a key cause of reduced CBF, microinfarcts, microbleeds, blood-brain barrier (BBB) dysfunction, and abnormalities of the perivascular space-is also driven by hypertension. 5,14,[25][26][27][28][29] Both large vessel disease and small vessel disease promote the vascular component of reduced brain health: loss of cognitive reserve, cognitive impairment, dementias, and neurodegeneration (Figure 1).…”
Section: Compendium: Circadian Mechanisms In Cardio/ Cerebrovascular ...mentioning
confidence: 99%
“…Hypertension, particularly during midlife, is a leading risk factor for cognitive decline and some forms of neurodegeneration. 5,7,24,26,203 The risk for hypertension-associated cognitive dysfunction may be even greater in Black and Hispanic individuals compared with White individuals. 204 Interestingly, attention to this relationship has revealed that the link between hypertension and cognition may begin earlier in life than previously appreciated, even in childhood.…”
Section: Circadian Influences In the Context Of Brain Healthmentioning
confidence: 99%
See 3 more Smart Citations